Fogo nas matas ripárias do Cerrado: comparação da avifauna entre áreas queimadas ou não - Pessini, Liliane Gomes Freitas (Universidade Federal de São Carlos, 2025)
Throughout Earth's evolutionary history, fire has been a natural force shaping terrestrial ecosystems. In the Cerrado, it regulates open vegetation and prevents woody encroachment, acting as a key element in the dynamics of savanna landscapes. However, humans have been altering fire regimes, intensifying wildfires and affecting sensitive ecosystems such as riparian forests. These forests play an essential role in landscape stability, serving as refuges for various species and acting as natural fire breaks. In this study I compared the vegetation and avifauna between burned and unburned riparian forests in the state of São Paulo, Brazil. Burned forests showed increased tree mortality and reduced canopy cover, with more light and invasion of highly flammable exotic grasses. Regarding bird communities, burned forests showed more forest-independent species and less insectivores than unburned forests, likely reflecting changes in environmental conditions and resource availability. These results suggest the vulnerability of at least part of the vegetation and bird fauna of riparian forests to human-induced fires and highlight the need for effective management strategies. Recognizing fire as a key ecological process and adopting fire management practices, we can contribute to Cerrado conservation, ensuring its resilience amid growing environmental threats.
Fire in the riparian forests of the Cerrado: comparison of avifauna between burned and unburned areas
Keywords: Comunidade de aves; Fogo; Incêndios antrópicos; Manejo do fogo; Matas ripárias; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA APLICADA